EARNINGS QUALITY: BUKTI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - EVELYNE HIOEMAWAN; PAULINA SUTRISNO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This study aims to obtain empirical evidence regarding the factors influencing earnings quality. This study uses six variables: profitability, firm size, investment opportunity set, managerial ownership, institutional ownership, and leverage on earnings quality. This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) for three consecutive years, from 2021 to 2023. The research sample used a purposive sampling method, resulting in 240 data points from 80 companies. The statistical method used in this study is OLS multiple regression with robustness standard errors. The results of this study indicate that profitability has a negative effect on earnings quality, while leverage has a negative impact on earnings quality. However, firm size, investment opportunity set, managerial ownership, and institutional ownership do not affect earnings quality.